Thyroid hormone receptor (TR)alpha and TRbeta expression in breast cancer - Ditsch, Nina; Toth, Bettina; Himsl, Isabelle; Lenhard, Miriam; Ochsenkühn, Robert; Friese, Klaus; Mayr, Doris; Jeschke, Udo (Histology and histopathology, 2013)
There is evidence that breast cancer patients suffer from thyroid disorders. However, the relation between thyroid receptor (TR) expression and breast cancer remains unknown so far. Therefore, the aim of this study was an immunohistochemical analysis of TR expression in breast cancer patients. - MATERIALS AND METHODS: The expression of the combined antibody TRalpha1 and 2 and TRalpha1 or 2 alone as well as the expression of combined TRbeta1 and 2 and TRbeta1 or 2 alone was investigated with specific monoclonal or polyclonal antibodies in 82 patients. All patients presented with a first diagnosis of sporadic breast cancer. The ABC method was used for staining and staining intensities were analyzed using the IRS score. - RESULTS: Both TRalpha and TRbeta were expressed in the nuclei of breast cancer cells. In 24% (28/78) of the slides TRalpha1 and 2 IRS was positive. Immunopositivity for TRalpha1 was found in 55/78 slides, for TRalpha 2 in 54/79 slides (71 and 68%, respectively). The expression of TRbeta1 and 2 showed a positive detection in 33/77 (43%) of the slides, for TRbeta1 it was 43/79 (54%), for TRbeta2 60/76 (79%). Significant correlations of the expression of TRs - especially TRalpha2 - were found with further prognostic histopathological parameters such as tumor size, axillary lymph node involvement, grading and hormone receptor status. Multivariate analysis showed a trend for TRalpha2 as an independent predictor of disease-free and overall survival. - DISCUSSION: Our results revealed specific alterations in the expression of TRs - especially of TRalpha2 - in breast cancer patients, suggesting it as a marker with possible prognostic validity.